ANALISIS STRATEGI PEMASARAN TOKO MEBEL UD BAROKAH DALAM MENINGKATKAN PENDAPATAN - Ahmad Masyhur; Abdul Qodir; Mohammad Abdillah (Jurnal Bina Bangsa Ekonomika, 2024)
Marketing strategy is very important to achieve store goals, therefore marketing plays a big role in realizing the mission of UD Barokah furniture store. Seeing this, UD Barokah furniture needs to have an ideal strategy for businesses to compete in the furniture and furniture industry in Besuk District. This research aims to make businesses competitive, in getting profits to maintain business. This type of research is descriptive of a qualitative nature. Data collection techniques carried out are interviews, observation, and documentation. The analysis technique used is In data management, the author uses three stages, namely data reduction, data presentation, and verification. The results of this study resulted in the conclusion that the results shown from the marketing strategy analysis and reflected the strategic solutions needed by the 7p mix in furniture and furniture stores to face competition and fix their shortcomings and increase revenue to be more optimal than the previous one